2017
DOI: 10.1123/jmld.2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

The Applicability of a Short Form of the Körperkoordinationstest für Kinder for Measuring Motor Competence in Children Aged 6 to 11 Years

Abstract: This study aimed to determine if the Körperkoordinationstest für Kinder (KTK) remained a valid assessment of motor competence following the removal of the hopping for height subtest (KTK3). Children (n = 2479) aged 6–11 years completed all KTK subtests (KTK4) and motor quotient sum scores (MQS) were determined for the KTK3 and KTK4. Classifications were established as MQS below percentile 5 (P5), MQS between percentile 5–15 (P15), MQS between percentile 15–50 (P15–50), MQS between percentile 50–85 (P50–85), MQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 11 publications
(24 reference statements)
0
50
0
Order By: Relevance
“…Studies evaluating the validity and reliability of FMS assessment tools were conducted in 29 countries, with Australia hosting the most studies (13) [ 50 , 56 , 71 77 ], followed by Brazil (12 studies) [ 53 , 57 , 66 , 70 , 78 85 ] and the USA (nine studies). Eight studies were carried out in Belgium [ 49 , 58 , 63 , 86 89 ] and seven in Canada [ 43 , 54 , 60 , 90 94 ]. The remaining 23 countries spanned Europe (23 studies from 15 countries), Asia (10 studies from 7 countries), South America (one study from Chile) and Africa (one study conducted in South Africa).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies evaluating the validity and reliability of FMS assessment tools were conducted in 29 countries, with Australia hosting the most studies (13) [ 50 , 56 , 71 77 ], followed by Brazil (12 studies) [ 53 , 57 , 66 , 70 , 78 85 ] and the USA (nine studies). Eight studies were carried out in Belgium [ 49 , 58 , 63 , 86 89 ] and seven in Canada [ 43 , 54 , 60 , 90 94 ]. The remaining 23 countries spanned Europe (23 studies from 15 countries), Asia (10 studies from 7 countries), South America (one study from Chile) and Africa (one study conducted in South Africa).…”
Section: Resultsmentioning
confidence: 99%
“…One found poor correlations between subtests (r ranged from .08 -.45) [156], and the other reported moderate correlations between tasks in a sample of children with ADHD (r ranged from .12 -.98) [62]. A modified version of the KTK (with hopping for height removed) was also compared to the standard KTK, which was found to have high levels of validity [89]. One study used Pearson Table 7.…”
Section: Concurrent Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…Gross motor skills were evaluated using three subtests (jumping sideways, moving sideways, and backwards balancing) of the Korper Koordinationstest für Kinder (KTK) (Kiphard & Schilling, 2007 ). The KTK originally consists of four subtests, but a recent study has shown substantial agreement between the test battery consisting of three subtests and the original test battery consisting of four subtests (Novak et al, 2017 ). Additionally, one item of the Bruininks-Oseretsky Test of Motor Proficiency, Second Edition (BOT-2; Bruininks & Bruininks, 2005 ) was used to measure ball skills.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, one item of the Bruininks-Oseretsky Test of Motor Proficiency, Second Edition (BOT-2; Bruininks & Bruininks, 2005 ) was used to measure ball skills. Both test batteries have shown to be reliable and valid for primary school children (Bruininks, 2005 ; Bruininks & Bruininks, 2005 ; Kiphard & Schilling, 2007 ; Novak et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%